Alcohol Abuse in Older Adults: An Invisible Population. (November 2014) - Alpert, Patricia T.
Alcohol abuse among older adults is known as the hidden epidemic as the number of individuals who suffer from dependency and abuse has about doubled in the last decade. Because baby boomers were more liberal substance users during the 1960s and 1970s, experts anticipate the epidemic will increase even further by 2020. Definition of abuse and screening as a preventive measure to identify alcohol abuse in older adults are explored.